Motivasi Karir, Motivasi Gelar, Persepsi Biaya Pendidikan, Parental Influence dan Minat Mengikuti PPAk - Munthe, Rodame; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi, 2021)
Accounting profession education is important because it can produce professional accountants, but the interest in following it is currently still low. This study aims to determine the effect of career motivation, degree motivation, perceived cost of education, and parental influence on interest in pursuing accounting profession education. The population is all active students of accounting in the morning and evening regular FEB Unud class of 2017 as many as 287. The sample collection technique is the purposive sampling method. The number of samples is 143 with the data collection method using a questionnaire. The data analysis technique is multiple linear regression analysis. The results of the analysis show that career motivation and degree motivation have an effect on interest in attending accounting profession education, perceptions of educational costs and parental influence have no effect on interest in PPAk. Keywords: Career Motivation; Degree Motivation; Perceptions of Education Costs; Parental Influence; Accountant Professional Education.